2018
DOI: 10.3389/fimmu.2018.02793
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, Bioinformatics and Structure-Function Antigen Mining For Gonorrhea Vaccines

Abstract: Expanding efforts to develop preventive gonorrhea vaccines is critical because of the serious health consequences combined with the prevalence and the dire possibility of untreatable gonorrhea. Reverse vaccinology, which includes genome and proteome mining, has proven successful in the discovery of vaccine candidates against many pathogenic bacteria. Here, we describe proteomic applications including comprehensive, quantitative proteomic platforms and immunoproteomics coupled with broad-ranging bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 204 publications
0
13
0
Order By: Relevance
“…A similar approach based on reverse vaccinology has also been applied for the identification of vaccine targets in K. oxytoca , another closely related species to K. pneumoniae [76]. Furthermore, this approach has been adopted to target other gram-negative pathogens such as Acinetobacter baumannii [28,77], Pseudomonas aeruginosa [78], Neisseria gonorrhoeae [79], etc.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach based on reverse vaccinology has also been applied for the identification of vaccine targets in K. oxytoca , another closely related species to K. pneumoniae [76]. Furthermore, this approach has been adopted to target other gram-negative pathogens such as Acinetobacter baumannii [28,77], Pseudomonas aeruginosa [78], Neisseria gonorrhoeae [79], etc.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an effective FDA-approved prophylactic against N. gonorrhoeae infections, new strategies are needed to expand the pool of candidates considered for potential clinical vaccine development. One innovative approach is reverse vaccinology antigen mining using a combination of high-throughput quantitative proteomics and bioinformatics (recently reviewed in [ 58 ]). The utility of proteomic technology has been clearly demonstrated in the discovery of N. gonorrhoeae lipoprotein MetQ (NGO2139).…”
Section: Resultsmentioning
confidence: 99%
“…Using high-throughput proteomics and immunoblotting analyses, we previously reported that MetQ is ubiquitously expressed in diverse Ng isolates [13,28,29,31], in host-relevant growth conditions [13] and in naturally released outer membrane vesicles [13,28]. In addition to a traditional lipoprotein signal peptide, MetQ contains a NlpA domain homologous to the respective domain in the E. coli methionine binding protein MetQ, NlpA [14,32]. Indeed, Ng MetQ binds L-methionine with nanomolar affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Serum or vaginal wash samples were serially diluted in PBS supplemented with 0.05% Tween (PBST) and added to each well. Polymorphism, phylogenetic, and allele mapping analyses were performed as described by[32], with the following exceptions. Briefly, the nucleotide sequence of metQ (ngo2139) was used to query the public Neisseria /pubmlst.org/neisseria/) to identify metQ alleles and nucleotide polymorphic sitesacross 4,421 isolates of N. gonorrhoeae for which metQ sequence data exist, as well as among all Neisseria isolates present in the database (21,798 isolates with metQ sequence data as of March 26, 2020).…”
mentioning
confidence: 99%